(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2025)
ABSTRACT. This article describes some of the problems encountered in the translation of scientific and technical terms that are relevant today and their causes. In fact, not only students, but also specialists face a number of difficulties when translating scientific and technical texts, because it is important to learn the terms of that particular field along with a set of general words in the translation.